2023
DOI: 10.26656/fr.2017.7(s1).26
|View full text |Cite
|
Sign up to set email alerts
|

3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitory activity of Indonesian Cajanus cajan leaves and Zingiber officinale extracts

Abstract: One indicator of antihypercholesterolemic candidates is their inhibitory activity on 3hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase enzyme. This study aimed to analyze the HMG-CoA reductase inhibitory activities of Cajanus cajan leaves, Zingiber officinale var Amarum and Zingiber officinale var Rubrum. C. cajan leaves and two types of Z. officinale were extracted using the maceration method with three solvents: distilled water, 70% ethanol and 96% ethanol. All nine types of resulted extracts were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…It has been reported that the 96% ethanol extract of C. cajan leaves extract from Lombok contains flavonoids, saponins, tannins, and steroids (Wresdiyati et al, 2020a). Similarly, the 96% ethanol extract of ginger (Z. officinale) var.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the 96% ethanol extract of C. cajan leaves extract from Lombok contains flavonoids, saponins, tannins, and steroids (Wresdiyati et al, 2020a). Similarly, the 96% ethanol extract of ginger (Z. officinale) var.…”
Section: Resultsmentioning
confidence: 99%
“…amarum rhizome were dried in the oven at 45°C for two days and one night, then they were grounded and filtered separately at a size of 80 mesh. The powdered pigeon pea leaves and ginger were extracted using 96% ethanol and maceration methods separately, as described by Wresdiyati et al (2015a;2020a). The two extracts were evaporated separately to get two dry extracts.…”
Section: Extraction Of Pigeon Pea Leaves and Gingermentioning
confidence: 99%
See 2 more Smart Citations
“…Struktur cincin hidrofobik dari statin menghubungi residu dalam heliks L1 dan L10 dari domain besar enzim . Tidak ada bagian yang memanjang Situs pengikatan NADP(H) ditempati oleh statin [12]. Struktur yang disajikan di sini menggambarkan hal itu statin menghambat HMGR dengan mengikat aktif situs enzim, sehingga mencegah secara sterik substrat dari pengikatan.…”
Section: Hasil Dan Pembahasanunclassified